The Transformation of Religious Literacy in the Digital Era: Empirical Findings from Tebuireng Islamic Boarding School, Indonesia - Rafi Jauhari Robbani (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: Analyze the transformation of religious literacy in the Tebuireng Islamic Boarding School in the digital era, the factors that affect it, and its impact on the religious understanding of students. The research also examines the integration of pesantren traditions with the development of digital technology. Theoretical framework: The research combines digital literacy theory, Islamic boarding school religious literacy, and educational sociology. The constructivist approach is used to understand the process of forming religious knowledge through the interaction of students with teachers, books, and digital media. Literature review: Previous studies have shown that digitalization increases access to religious learning resources, but also raises the challenge of information validity. Studies on digital literacy transformation in large Islamic boarding schools such as Tebuireng are still relatively limited. Methods: The research uses a qualitative approach through interviews, observations, and documentation. The data were analyzed by reduction, categorization, and thematic interpretation techniques to find patterns of religious literacy transformation. Results: The results of the study show an increase in the use of digital books, video platforms, and online media in learning. Nevertheless, the tradition of talaqqi and the study of the yellow book remain the main basis for religious learning. Implications: Digitalization has the potential to strengthen students' religious literacy if supported by a directed curriculum and teacher supervision. These findings can be a reference for other Islamic boarding schools in developing digital adaptation strategies. Novelty: This study offers a comprehensive field study on the transformation of religious literacy in the Tebuireng Islamic Boarding School. Focusing on the integration of pesantren traditions and digital technology is a new contribution to the study of pesantren literacy.